TINDAK TUTUR DIREKTIF DAN EKSPRESIF DALAM MARIO TEGUH SUPER SHOW DI MNCTV - Faizah, Hasnah; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study discusses the directive and Expressive Speech Acts in Mario Super Show in MNCTV . This study also discusses the description and the directive speech acts expressive speech acts found in the event Mario Super Show in MNCTV . This study used a qualitative approach and descriptive method that aims to describe the directive and expressive speech acts contained in the event Mario Super Show in MNCTV . The results of the research in the form of a description of the directive speech acts and expressive speech acts found in the event Mario Super Show in MNCTV .Keywords : Speech acts directive , expressive speech acts , Mario Teguh Super Show